Pelvic Floor Muscle Exercise pada Pasien Post Radikal Prostatektomi dalam Menurunkan Inkontinensia Urine dan Kualitas Hidup - Yogo Apriyanto; Tintin Sukartini; Sri Purwanti; Ratu Izza AM (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of Pelvic Floor Muscle Exercise (PMFE) on urinary incontinence and quality of life (QOL) in post-radical prostatectomy prostate cancer patients. This research method is a systematic review by searching literature through several indexed electronic databases (Scopus, Science Direct, CINAHL, PubMed, ProQuest, SAGE, Springer Link). The study results were obtained from 10 articles on pelvic floor muscle exercise (PFME) modality therapy. Eight pieces explained that PFME without a combination effectively reduced urinary incontinence and improved the quality of life (QOL) of post-RP patients; one article explained the effectiveness of the variety of PFME with electrical stimulation in reducing incontinence urine in post-RP patients. One article describes the combination of PFME with the WeChat application reducing urine leakage and improving urinary continence. In conclusion, Pelvic Floor Muscle Exercise (PFME) is a therapy that is effective for urinary incontinence and men's quality of life after radical prostatectomy (RP). Keywords: Urinary Incontinence, Pelvic Floor Muscle Exercise, Radical Prostatectomy